2019
DOI: 10.1002/pro.3738
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into Acyl‐coenzyme A binding domain containing 3 (ACBD3) protein hijacking by picornaviruses

Abstract: Many picornaviruses hijack the Golgi resident Acyl-coenzyme A binding domain containing 3 (ACBD3) protein in order to recruit the phosphatidylinositol 4-kinase B (PI4KB) to viral replication organelles (ROs). PI4KB, once recruited and activated by ACBD3 protein, produces the lipid phosphatidylinositol 4-phosphate (PI4P), which is a key step in the biogenesis of viral ROs. To do so, picornaviruses use their small nonstructural protein 3A that binds the Golgi dynamics domain of the ACBD3 protein. Here, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…While PHB and APOLs seem to be part of an autophagy system linked to infection, PI4KB is likely to be associated with this system given involvement of this enzyme in both autophagy and viral replication [56,118–131]. Accordingly, PI4KB was found to be involved in autophagy linked to infection by group A Streptococcus [144].…”
Section: Apols and Viral Infectionmentioning
confidence: 99%
“…While PHB and APOLs seem to be part of an autophagy system linked to infection, PI4KB is likely to be associated with this system given involvement of this enzyme in both autophagy and viral replication [56,118–131]. Accordingly, PI4KB was found to be involved in autophagy linked to infection by group A Streptococcus [144].…”
Section: Apols and Viral Infectionmentioning
confidence: 99%
“…Aichi virus (AiV), a member of the kobuvirus genus in the Picornaviridae family, is one of the pathogenic factors of gastroenteritis. Researchers demonstrated that the non-structural proteins 2B, 2BC, 2C, 3A, and 3AB from Aichi virus interacted with ACBD3 and PI4KB to form a protein complex at ROs to promote PI4P synthesis (Greninger et al, 2012;Sasaki et al, 2012;Klima et al, 2017;McPhail et al, 2017;Chalupska et al, 2019). Silencing of ACBD3 or PI4KB inhibited viral replication by about 70% (ACBD3) or 99% (PI4KB).…”
Section: Acbd3 In Kobuvirus Infectionmentioning
confidence: 99%
“…PI4KB localizes to the Golgi apparatus by interacting with ACBD3. In cells infected by AiV, the viral proteins 2B, 2BC, 2C, 3A, and 3AB compete with Golgi giantin to bind to ACBD3, causing viral protein/ACBD3/PI4KB formation, and the colocalization of giantin and ACBD3 disappears (Greninger et al, 2012;Sasaki et al, 2012;Klima et al, 2017;McPhail et al, 2017;Chalupska et al, 2019).…”
Section: Acbd3 In Kobuvirus Infectionmentioning
confidence: 99%
See 2 more Smart Citations